Anal Ureaplasma spp. positivity among HIV positive men who have sex with men may be associated with high-risk-type HPV infections. (July 2019) - Borena, Wegene; Kruis, Simon; Kitchen, Maria; Taylor, Ninon; Gisinger, Martin; Oberkofler, Hannes; Stoiber, Heribert; Zangerle, Robert; von Laer, Dorothee; Sarcletti, Mario
Highlights: One-in-five HIV-positive men having sex with men harboured anal Ureaplasma spp. Ureaplasma Urealyticum was more commoly detected that Ureaplasma parvum . Men positive for hrHPV-genotypes were highly likely harbour Ureaplasma spp as compared to men negative for hrHPV. A multiplex-STI-screening-approach may be considered in monitoring STI including Ureaplasma spp. among HIV infected MSM. Abstract: Objective: HIV positive individuals, particularly men having sex with men (MSM), are at increased risk of sexually transmitted infections (STIs) at genital and extra-genital sites. Data on anorectal Ureaplasma infections are lacking. The aim of our study was to characterize anal Ureaplasma positivity among a cohort of HIV positive MSM and evaluate possible association with papillomavirus infection at the same site. Methods: Anal swab samples, collected as part of routine screening for Chlamydia trachomatis and Neisseria gonorrhea, were additionally tested for HPV genotypes as well as for Ureaplasma and Mycoplasma using nucleic acid amplification method. Results: Out of a total of 222 study participants, 195 (89%, 95% CI (84.9–93.2)) were positive for HPV, approximately three quarter being high-risk genotypes. Forty three individuals (19.4%, 95% CI (14.4–24.3)) harbored Ureaplasma spp. Infection with high-risk HPV types was significantly associated with co-presence of Ureaplasma with an odds ratio (95% confidence-interval) of 2.59 (1.03–6.54), P = 0.04. Conclusion: Besides a high predominance of HPV infection, asymptomatic HIV positive MSM had a high prevalence of anal Ureaplasma positivity. Concomitant infections with high-risk HPV genotypes were common and statistically significant. The role of this co-existence as a potential risk factor for anal carcinogenesis needs further elucidation.